Evaluation of the Initial 12months of a Routine Cryptococcal Antigen Screening Program in Reduction of HIV-Associated Cryptococcal Meningitis in Uganda - Enock, Kagimu; Kiwanuka, Julius; Abila, Derrick Bary; Rutakingirwa, Morris K.; Kasibante, John; Kiiza, Tadeo Kandole; Kwizera, Richard; Semeere, Aggrey; Meya, David B. (BMC Health Services Research, 2022)
Asymptomatic Cryptococcal Antigenemia (CrAg) patients develop meningitis within a month of testing positive. Pre-emptive antifungal therapy can prevent progression to Cryptococcal meningitis (CM). In April 2016, a national CrAg screening program was initiated in 206 high-volume health facilities that provide antiretroviral therapy in Uganda. We report the evaluation of the CrAg screening cascade focusing on linkage to care, fluconazole therapy for 10 weeks and 6 months follow up, and ART initiation in a subset of facilities. We conducted a retrospective, cross-sectional survey of patients with CD4 < 100 at seven urban and seven rural facilities after 1 year of program implementation. We quantified the number of patients who transitioned through the steps of the CrAg screening cascade over six-months follow-up. We defined cascade completion as a pre-emptive fluconazole prescription for the first 10 weeks. We conducted semi-structured interviews with lab personnel and clinic staff to assess functionality of the CrAg screening program. Data was collected using REDCap. We evaluated 359 patient records between April 2016 to March 2017; the majority (358/359, 99.7%) were from government owned health facilities and just over half (193/359, 53.8%) had a median baseline CD4 cell count of < 50 cell/μL. Overall, CrAg screening had been performed in 255/359 (71.0, 95% CI, 66.0–75.7) of patients’ records reviewed, with a higher proportion among urban facilities (170/209 (81.3, 95% CI, 75.4–86.4)) than rural facilities (85/150 (56.7, 95% CI, 48.3–64.7)). Among those who were CrAg screened, 56/255 (22.0, 95% CI, 17.0–27.5%) had cryptococcal antigenemia, of whom 47/56 (83.9, 95% CI, 71.7–92.4%) were initiated on pre-emptive therapy with fluconazole and 8/47 (17.0, 95% CI, 7.6–30.8%) of these were still receiving antifungal therapy at 6 months follow up. At least one CNS symptom was present in 70% (39/56) of those with antigenemia. In patients who had started ART, almost 40% initiated ART prior to CrAg screening. Inadequacy of equipment/supplies was reported by 15/26 (58%) of personnel as a program barrier, while 13/26 (50%) reported a need for training about CM and CrAg screening. There was a critical gap in the follow-up of patients after initiation on fluconazole therapy. ART had been initiated in almost 40% of patients prior to CrAg screening.. Higher antigenemia patients presenting with CNS symptoms could be related to late presentation. There is need to address these gaps after a more thorough evaluation.